Pola Pendidikan Ekonomi Masyarakat Nelayan Pesisir Puger yang Terintegrasi dalam Kearifan Lokal Petik Laut - Arie Eko Cahyono (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the patterns of informal economic education in the coastal fishing community of Puger, Puger District, Jember Regency, integrated into the Petik Laut local wisdom. Using a descriptive qualitative approach with a case study method, data were collected through in-depth interviews with 25 informants, six months of participatory observation, and documentation studies. The Miles and Huberman interactive model was employed for data analysis. The findings identify four patterns of informal economic education: (1) economic gratitude education (nyadheren rejeki); (2) economic mutual cooperation education (saling bantu); (3) local entrepreneurship education based on marine product processing; and (4) maritime economic sustainability education (sagara panguripan). Value transfer occurred through role modeling, habituation, and direct participation. The Petik Laut local wisdom functions as a hidden curriculum that shapes economic awareness, basic financial literacy, maritime work ethic, and sustainable economic behavior among the Puger fishing community.